Effect of temperature, rainfall and planting date on aflatoxin and fumonisin contamination in commercial Bt and non-Bt corn hybrids in Arkansas - Abbas, Hamed; Shier, W.; Cartwright, Rick (Phytoprotection, 2007)
Corn (maize, Zea mays) is susceptible to contamination with aflatoxins, fumonisins and other mycotoxins, particularly in the southeastern USA. In principle, mycotoxin contamination could be reduced in commercial corn hybrids with shorter growing seasons by planting at dates which minimize plant stress during the critical kernel-filling period. To evaluate this strategy, commercial Bt and non-Bt hybrids were planted in Arkansas in mid-April and early May of 2002, 2004 and 2005. The mid-April planting date resulted in lower aflatoxin contamination in harvested corn each yr and in significantly less frequent contamination above a regulatory action level in 2005 and overall than did the early-May planting date in both Bt and non-Bt corn. The mid-April planting date resulted in significantly lower total fumonisin contamination in harvested corn and in less frequent contamination above a regulatory advisory level than the early May planting date in 2 of 3 yr and overall in both Bt and non-Bt corn. All fumonisin subtypes studied were reduced. Frequent co-occurrence of aflatoxin and fumonisin was observed. Fumonisin levels averaged lower in Bt hybrids than in non-Bt hybrids at all plantings. Reduced aflatoxin and fumonisin contamination with mid-April planting could not be explained by any measure of heat stress during the kernel-filling period.